Irreversible furin cleavage site exposure renders immature tick-borne flaviviruses fully infectious - Holoubek, Jiří; Salát, Jiří; Matkovic, Milos; Bednář, Petr; Novotný, Pavel; Hradilek, Martin; Majerová, Taťána; Rosendal, Ebba; Eyer, Luděk; Fořtová, Andrea; Beránková, Michaela; Bell-Sakyi, Lesley; et al. (Nature communications, 2025)
Flavivirus assembly is driven by the envelope glycoproteins pre-membrane (prM) and envelope (E) in the neutral pH environment of the endoplasmic reticulum. Newly budded, spiky particles are exported through the Golgi apparatus, where mildly acidic pH induces a major surface rearrangement. The glycoproteins reorganize into (prM/E)\₂ complexes at the surface of smooth particles, with prM trapped at the E dimer interface, thereby exposing a furin cleavage site (FCS) for proteolytic maturation into infectious virions. Here, we show that in the absence of furin, immature tick-borne flavivirus particles—tick-borne encephalitis virus, Langat virus, and Louping ill virus—remain fully infectious and pathogenic in female BALB/c mice, in contrast to mosquito-borne flaviviruses such as Usutu, West Nile, and Zika viruses. We further show that the FCS in tick-borne viruses remains exposed at neutral pH, allowing furin at the surface of target cells to activate viral fusogenicity, while mosquito-borne counterparts require acidic re-exposure. Mutations increasing the dynamic behavior of the E dimer mimic the mosquito-borne phenotype, with retracted FCS at neutral pH and loss of infectivity. Our multidisciplinary approach—combining virological assays, targeted mutagenesis, structural modeling, and molecular dynamics simulations—highlights the role of E dimer dynamics in regulating flavivirus maturation and infectivity. Immature particles of flaviviruses transmitted by mosquitoes are known to be non-infectious. Here, the authors show that immature tick-borne flaviviruses stay infectious in vivo and using structural modeling they resolve unique structural features that distinguish tick-borne from mosquito-borne flaviviruses.